Judicial Oversight and the Role of the Comptroller General in Insolvency Disclosure: A Normative Analysis of the Jordanian Companies Act - Boutosh, Ahmad (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2024)
This study aims to clarify the legal framework and procedural steps required for the Comptroller General of Companies in Jordan to request the disclosure of insolvency applications, as well as the oversight conditions and judicial controls applied to these powers. Employing a normative legal research method, the study analyzes relevant legislative texts, focusing on Article 193 of the Jordanian Companies Act, to elucidate the comptroller’s authority to enforce compliance and monitor companies’ adherence to statutory obligations from the point of registration onward. The study’s findings indicate that the comptroller derives explicit authority under Article 193 to submit insolvency notifications, highlighting an imperative for additional punitive measures against companies that obstruct the comptroller’s oversight. This enhancement is essential for fortifying both preventative and punitive regulatory functions, thus promoting early identification of corporate insolvency risks and strengthening governance. The study implies that reinforcing the comptroller’s oversight powers with stricter enforcement mechanisms would significantly improve regulatory efficacy, encouraging a more transparent and accountable corporate sector in Jordan.